The prediction of financial performance in dependence on the type of organisational culture - Miloslava Hiršová; Lenka Komárková; Petr Pirožek (Trends Economics and Management, 2018)
Purpose of the article: Knowing the factors that affect organisation's performance is a prerequisite for successful management. But it should be remembered that these factors do not act separately and that it is always necessary to examine the manner in which they interact and the level of synergy they can create. Our paper is based on the assumption that these requirements can by met by applying a typology of the organisational culture (OC). Methodology/Methods: Here we evaluate the return on assets (ROA) indicator in relation to different types of the OC based on four-dimensional Harrison and Handy's model in 194 organisations operating in the Czech Republic, using quantitative methods including multiple regression analysis. Scientific aim: The aim of the paper is not only to find a response to whether there is a relationship between the different types of organisational culture and the financial performance of the organisation. We also want to point out at the possibilities of deeper analysis and interpretation of the factors that the typology of organisational culture includes. Findings: Our results show that there is a positive significant correlation between the task type of the OC and ROA and a negative one between the power type of the OC and ROA. Conclusions: This suggests that selecting the task type of the OC may lead to improvements of financial indicators, but there are also other factors that must be taken into consideration.
Keywords: L20; M21; 650; organizational culture; Handy's typology; task type of OC; financial performance; ROA